Development of Bulletin-Integrated Character Education (BICE) Media to Enhance and Assess Scientific Literacy - Azzajjad, Muhammad Fath; Diah, Anang Wahid M.; Afadil; Rahmawati, Sitti; Astija; Ahmar, Dewi Satria (PT Mattawang Mediatama Solution, 2026)
In higher education, scientific literacy is still a significant difficulty, especially when instruction focuses on procedural knowledge without including moral principles. The purpose of this study was to create and examine Bulletin-Integrated Character Education (BICE) as a teaching tool to improve and gauge students' scientific literacy. The requirement for educational materials that simultaneously promote character development and higher-order thinking makes this research urgent. In order to produce verified educational media, this study used a Research and Development (R&D) approach based on the Hannafin and Peck paradigm. According to expert validation, the BICE media was highly reliable (Cronbach's ? = 0.88–0.92) and valid (CVI = 0.92–0.95). Strong dependability was also shown by the scientific literacy test (? = 0.92). Students who were taught PBL–BICE fared better than those who were taught PBL alone, according to inferential analysis, with a significant effect size (d = 1.12). Conceptual literacy was a strong predictor of multidimensional literacy, according to correlation and regression analyses (r = 0.71; ? = 0.48). These results suggest that in order to foster advanced scientific literacy in higher education, character-based media should be incorporated into problem-based learning.